The global burden of age-related hearing loss among individuals aged 60 years and older: An analysis for the global burden of disease study 2021 and predictions to 2050 - Peng Zhou; Huiqin Wu; Kui Xu; Xin Pan; Ling Li (PLoS ONE, 2026)
Objectives Age-related hearing loss (ARHL) impacts communication, cognitive function, and mental health, with regional prevalence variation. We analyzed global spatial and temporal trends in ARHL burden from 1990 to 2021. Methods Data on ARHL prevalence and years lived with disability (YLDs) among individuals aged 60 and older were analyzed. Estimated annual percentage changes (EAPC) in the age-standardized prevalence (ASPR) and YLD rates (ASYR) were analyzed by country, gender and socio-demographic index (SDI). Age-period-cohort, decomposition analyses, and frontier analysis identified influencing factors and quantify inequalities. Future trends were predicted using Bayesian model. Results From 1990 to 2021, global ARHL prevalence cases increased by 137.43% (302.79 million to 718.93 million), with a 4.34% rise in ASPR. YLDs grew by 144.3% (10.76 million to 26.30 million), and ASYR rose by 4.45%. Males exhibited higher ASPR and ASYR despite more cases among females. High-middle and middle SDI regions showing higher and steadily increasing ASPR and ASYR, while high SDI regions exhibited the lowest and most stable rates. Population growth was the primary driver of the increasing burden. Projections indicate continued growth in ARHL cases by 2050. Conclusions The ARHL burden among older adults has increased significantly, with marked regional and socio-demographic disparities. Lower SDI regions bear disproportionately higher burdens. Effective strategies, including public education, hearing protection, early screening, and research into treatments, are urgently needed to address this public health challenge.